Stakeholders’ perspectives, placemaking and tactical urbanism on the spatial reconfiguration of urban schools in Timişoara, Romania - Adelina Camelia Tuță; Alexandru Dragan; Remus Crețan; Melinda Dincă (Humanities & Social Sciences Communications)
Abstract Recent studies have highlighted that placemaking and tactical urbanism are key drivers in improving a school’s climate. This study explores the potential for enhanced spatial reconfiguration of educational institutions within a post-communist context, with the objective of gaining insight into the perceptions and involvement of relevant stakeholders. To this end, a comprehensive research approach was employed, encompassing focus groups, interviews, and a survey of school personnel, pupils’ parents, and local residents in the environments of Timisoara, Romania. The findings indicate that the implementation of changes to the school spaces and the neighbourhood environment could be more effectively achieved through the involvement of local stakeholders. The existing urban schools’ spatial patterns are not optimal, and changes to the reconfiguration of the school environment should be planned based on the collaboration of relevant stakeholders and on the specific needs of users of school places.